MERCURY DISTRIBUTION IN SEDIMENTS OF A SHALLOW TROPICAL RESERVOIR IN BRAZIL - Souza, Vinicius Andrade; Wasserman, Julio Cesar (Geochimica Brasiliensis, 2015)
Mercury is a toxic element that is globally distributed in contamina-ted areas, as well as remote environments. In the case of the Juturnaíba Lake (State of Rio de Janeiro, Southeastern Brazil), part of the landscape was flooded after the construction of a dam, favoring the development of anoxic conditions, reducing the redox potential within the sediments and modifying the geochemical conditions. The understanding of the pollutants behavior in the Juturnaíba is necessary, because the system is a multi purpose environment that is used for water supply, agricultural irrigation, leisure and fishing. In the present study, we evaluated the mercury distribution of superficial sediments of the Juturnaíba reservoir that was interpreted in the light of granulometry and concentrations of carbon and nitrogen. Thirty-two surface sediment samples were collected in March 2011 in order to carry out the total mercury analyses with Cold Vapor Atomic Absorption Spectrophotometry (CV-AAS). The distribution map indicates that the highest mercury values (211 ng/g) are associated with the presence of the aquatic macrophytes banks. The lowest values (58 ng/g) were observed in the Northern portion, associated with the inputs of the São João River that drains a better preserved area. It is necessary to underline that the highest concentrations occur in an area of significant macrophyte production, where methylation process may be more significant, constituting a threat for humans and the environment.